HYDROCARBON POLLUTION IN THE NORTH-WESTERN PART OF THE CASPIAN SEA - E. V. Ostrovskaya; E. V. Kolmykov; O. I. Kholina; T. S. Pronina; M. V. Voinova (Юг России: экология, развитие)
Aim. The paper is aimed to estimate the current level of hydrocarbon pollution of the marine environment in the North-Western part of the Caspian Sea.Methods. The paper discusses the results of three-year studies conducted in 2012-2014 within the framework of Roshydromet’s Programme of monitoring of transboundary waters of the Caspian Sea. Spatial distribution of concentrations of hydrocarbons (total and polyaromatic) in water and bottom sediments of the area was analysed. Concentrations of total hydrocarbons were determined by means of infrared spectrometry and PAHs – of gas chromatography with mass spectrometry.Results. The range of the total hydrocarbons in the area’s water is from slight traces to 240 µg/l, in sediments – from traces to 114 µg/g (dry weight). Total concentrations of PAHs in water varied from traces to 321 ng/l, in sediments – from traces to 699 ng/g (dry weight). For the source identification, data of satellite monitoring of the area were used. The data showed increasing input of hydrocarbons coming into the marine environment with discharges from vessels.Conclusion. The results of these studies are compared to those of previous research and show that the level of hydrocarbons in the area is typical for slightly polluted areas.